The Golden Girls Live: residual television texts, participatory culture, and queering TV heritage through drag. Issue 5 (2nd September 2016) - Patterson, Eleanor
Abstract: The SF Golden Girls have been producing live performances of The Golden Girls episodes in drag since 2005, creating an iterative form of fan productivity that consistently resonates with San Francisco audiences. This essay considers the cultural significance of the SF Golden Girls' live performances as a case study in how queer participatory culture can change the meanings of a residual media object. I argue that the participatory engagement between the audience members and the drag queen performers make The Golden Girls a collective and visible site of queer television heritage, and that producing The Golden Girls Live in drag also offers different logics of representation and engagement than television. These live performances are significant because The Golden Girls has become a symbol of television heritage, and performing episodes in drag explicitly queers a television program that has become a site of cultural memory and historical meaning. Additionally, these performances are staged in December as The Golden Girls: The Christmas Episodes, which restructures television heritage to create a new continuity between the past and present and construct a queered Christmas ritual that is familiar and imbued with historical consciousness.